SWEETs, transporters for intracellular and intercellular sugar translocation. (June 2015) - Eom, Joon-Seob; Chen, Li-Qing; Sosso, Davide; Julius, Benjamin T; Lin, IW; Qu, Xiao-Qing; Braun, David M; Frommer, Wolf B
Highlights: SWEETs are small transporters for sugars undergoing multiple conformational states during transport cycle. SWEET9 mediates nectar secretion. A SWEET–SUT pair mediates phloem loading. Select SWEETs play key roles in post-phloem unloading. SWEETs are key susceptibility gene for rice and cassava blight. Abstract : Three families of transporters have been identified as key players in intercellular transport of sugars: MSTs (monosaccharide transporters), SUTs (sucrose transporters) and SWEETs (hexose and sucrose transporters). MSTs and SUTs fall into the major facilitator superfamily; SWEETs constitute a structurally different class of transporters with only seven transmembrane spanning domains. The predicted topology of SWEETs is supported by crystal structures of bacterial homologs (SemiSWEETs). On average, angiosperm genomes contain ∼20 paralogs, most of which serve distinct physiological roles. In Arabidopsis, AtSWEET8 and 13 feed the pollen; SWEET11 and 12 provide sucrose to the SUTs for phloem loading; AtSWEET11, 12 and 15 have distinct roles in seed filling; AtSWEET16 and 17 are vacuolar hexose transporters; and SWEET9 is essential for nectar secretion. The remaining family members await characterization, and could play roles in the gametophyte as well as other important roles in sugar transport in the plant. In rice and cassava, and possibly other systems, sucrose transporting SWEETs play central roles in pathogen resistance. Notably, the human genome also contains a glucose transporting isoform. Further analysis promises new insights into mechanism and regulation of assimilate allocation and a new potential for increasing crop yield.